2020
DOI: 10.3390/ijms21031044
|View full text |Cite
|
Sign up to set email alerts
|

A Dietary Ketone Ester Normalizes Abnormal Behavior in a Mouse Model of Alzheimer’s Disease

Abstract: Because of a decreased sensitivity toward insulin, a key regulator of pyruvate dehydrogenase (PDH), Alzheimer’s patients have lower brain glucose utilization with reductions in Tricarboxylic Acid (TCA) cycle metabolites such as citrate, a precursor to n-acetyl-aspartate. In the 3xTgAd mouse model of Alzheimer’s disease (AD), aging mice also demonstrate low brain glucose metabolism. Ketone metabolism can overcome PDH inhibition and restore TCA cycle metabolites, thereby enhancing amino acid biosynthesis. A keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…A recent study in a mouse model of Alzheimer’s disease (triple transgenic Alzheimer’s 3xTgAD, which shows reduced brain glucose utilization) demonstrated that BHB ketone ester intervention, compared to a regular chow diet, elevated hippocampal glutamate and α-glutarate (a precursor of glutamate), and glutamate and α-glutarate levels intercorrelated positively in both groups. This may indicate that metabolic ketosis furnishes mitochondria with TCA cycle substrates ( 17 ). Furthermore, a 4-month KD elevated Glu and glutamine in young adult rats ( 36 ), and although human patients with epilepsy did not show differences in posterior cingulate cortical Glu measures compared to controls, elevated Glu concentrations predicted short-term freedom from seizures, hence indicating clinical relevance of elevated Glu in epilepsy ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in a mouse model of Alzheimer’s disease (triple transgenic Alzheimer’s 3xTgAD, which shows reduced brain glucose utilization) demonstrated that BHB ketone ester intervention, compared to a regular chow diet, elevated hippocampal glutamate and α-glutarate (a precursor of glutamate), and glutamate and α-glutarate levels intercorrelated positively in both groups. This may indicate that metabolic ketosis furnishes mitochondria with TCA cycle substrates ( 17 ). Furthermore, a 4-month KD elevated Glu and glutamine in young adult rats ( 36 ), and although human patients with epilepsy did not show differences in posterior cingulate cortical Glu measures compared to controls, elevated Glu concentrations predicted short-term freedom from seizures, hence indicating clinical relevance of elevated Glu in epilepsy ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…EKSs may exert these beneficial effects via increased ketone body level, which can improve mitochondrial functions. For example, increased level of βHB can compensate glucose hypometabolism-generated decrease in energy source in human and restore ATP synthesis [ 16 , 289 , 318 , 319 , 323 ]. In fact, glucose hypometabolism may contribute to the development of, for example, Alzheimer’s disease [ 324 , 325 ].…”
Section: Alleviating Effects Of Ketosis On Lifespan Aging and Age-relmentioning
confidence: 99%
“…The reaction mixture was filtered to remove the enzyme and evaporated under reduced pressure (80 mm Hg) to separate unreacted ethyl ester (S)-2 as the distillate (0.4 g, 3.0 mmol), 40% yield (91% ee), from the (R)-3-hydroxybutyl (R)-3-hydroxybutyrate (R,R)-4 (0.64 g, 3.6 mmol),48% yiled (>90% dr). 1…”
Section: Synthesis Of (R)-3-hydroxybutyl (R)-3-hydroxybutyrate 4 Frommentioning
confidence: 99%
“…The ketone bodies (R)-3-hydroxybutyrate and acetoacetate, are short chain acids produced by the liver from the free fatty acids released from adipose tissue. The blood ketone bodies concentration normally ranges below 1 mM [1] increasing up to 5−7 mM during prolonged fasts [2]. Under this metabolic condition, known as ketosis, ketone bodies efficiently replace glucose as respiratory substrate, furnishing a higher ATP yield with respect to pyruvate, the end-product of glycolysis [3].…”
Section: Introductionmentioning
confidence: 99%